SISTEM INFORMASI MANAJEMEN PERSEDIAAN BARANG BERBASIS WEB MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) STUDI PADA TOKO KUDUS JAYA - Andrew Listanto; Paulus Hartanto (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2018)
Merchandise inventory is the most important asset in the survival of a trading business or shop. Toko Kudus Jaya is a retail trading business that sells hundreds of types of nuts and bolts of various types and sizes. The problem is that this shop still uses manual records to record the inventory of merchandise. This is considered vulnerable to various kinds of recording errors such as excess or lack of inventory and also considered less effective because it takes a lot of time in the recording process. The next problem is the procedure of ordering goods that only rely on estimates of sales and are only done when the inventory has run out without taking into account other costs at the time of ordering. To solve these problems, the authors use Research And Development (R&D) as a research and product development method and the EOQ (Economic Order Quantity) method used to calculate the optimal order amount by calculating the cost of storing and ordering costs. The author designed a prototype of a web-based merchandise inventory management information system with the EOQ method, the PHP programming language, MySQL as the Database and the bootstrap framework as the user interface. The application of web-based technology with the EOQ method is expected to help the store in its work activities so that it gets integrated data in one database and can determine the number of orders so that it can save costs incurred when making an order.